The drill and practice application in teaching science for lower secondary students - Rathakrishnan, Mohan; Raman, Arumugam; Haniffa, Mohamed Ali; Mariamdaran, Saralah Devi; Haron, Azlina (Global Academic Excellence, 2018)
Teaching and learning science at school determine the academic achievement of lower secondary school students. In this study, the lower secondary students are referred to Form One. This study examines the effectiveness of using drill and practicing (DP) method on the performance and understanding of students in Science subjects on the topic “Cell As a Unit Of Life”. Most of Form 1 student could not analyse any practical activities to clarify the learning objectives and its’ concept. Without knowing the concept, the students memorized the science facts rather than applying meaningful learning. This weakness causes the students to fail to answer examinations questions and affect their performance.Drill and practicing methods was carried out to examine the students' performance and understanding on the topic.A total of 66 students of the Form One comprises of boy and girl students were selected using purposive random sampling. The sample was categorized as moderate student based on the UPSR (Ujian Penilaian Sekolah Rendah) results. Two-group experimental design is used in this study. The form of this study was chosen because it enable the researchers to collect information from two group The students were divided into experimental group (using drill and practice method) and the control group (using conventional method). The quantitative data collected through pretest, posttest and questionnaire were analysed using SPSS and presented as descriptive and inferential statistics.The analysis shows that the experimental group score a mean of 25.41 (SD = 7.04) (M = 25.41, SE = 0.704) while the control group reported a mean of 22.14 (SD=11), (M = 22.14, SE = 0.420).The experimental group also show better understanding on the cell unit (M = 16, SD = 5.66) compare to control group (M = 8, SD = 4.95). The finding indicate that the students who used the DP method in learning Cell unit shows higher performance achievement and understanding compare to the group who use conventional way of learning.Choosing or applying appropriate teaching methods in teaching process in order to achieve educational excellence shows that drilling and training method is effective in teaching and learning among the lower secondary students